2005
DOI: 10.1161/01.atv.0000190609.28293.17
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Angiogenesis With Intramuscular Injection of Low-Dose Recombinant Granulocyte-Colony Stimulating Factor

Abstract: Objective-In vivo administration of granulocyte colony-stimulating factor (G-CSF) has been shown to facilitate regeneration of cardiovascular tissues. However, G-CSF causes marked leukocytosis that potentially induces adverse cardiovascular events. Earlier studies showed that G-CSF had direct stimulatory actions on mature endothelial cells, resulting in promotion of angiogenesis. We thus examined whether low doses of recombinant human G-CSF (rhG-CSF) locally injected into ischemic tissues would stimulate angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 27 publications
1
33
0
2
Order By: Relevance
“…This likely reflects the fact that, in addition to its proliferative effect on granulation tissue, G-CSF also augmented the incidence of apoptosis. G-CSF is known to act as a growth factor toward myeloid progenitor cells and mature neutrophils, as well as some nonhematopoietic cell types (2), and to exert an angiogenic effect (4,15). The proliferative effect on granulation tissue, which includes vascular cells, is, therefore, not so surprising.…”
Section: Discussionmentioning
confidence: 99%
“…This likely reflects the fact that, in addition to its proliferative effect on granulation tissue, G-CSF also augmented the incidence of apoptosis. G-CSF is known to act as a growth factor toward myeloid progenitor cells and mature neutrophils, as well as some nonhematopoietic cell types (2), and to exert an angiogenic effect (4,15). The proliferative effect on granulation tissue, which includes vascular cells, is, therefore, not so surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al recently reported that a low dose of G-CSF (2-20 g/kg) in rats directly stimulates mature endothelial cells to migrate without mobilizing endothelial stem/progenitor cells. 17 The present study found that a low dose of G-CSF (2 g/kg) improved the survival of PAH rats, and that daily G-CSF administration did not increase circulating c-kit positive stem cells, which comprise hemangioblasts and hematogenic angioblasts. These findings suggest that in our model, G-CSF did not mobilize angiogenic stem/progenitor cells, which would engraft to injured pulmonary arteries from the BM into the circulation, but directly stimulated endothelial cells to proliferate and migrate in PA lesions in situ.…”
Section: Circulation Journal Vol71 January 2007mentioning
confidence: 43%
“…Between 200 and 300 g/kg per day of recombinant human G-CSF injected for 5 days into rats induced hematopoietic effects that are equipotent to those observed in humans given 10-20 g/kg per day for a similar period. 17 We consider that 100 g/kg per day of rhG-CSF corresponded to 5 g/kg per day in humans, which is used as a clinical dose. [18][19][20][21] Further investigation of other tissue-protective properties of G-CSF in this model, such as anti-apoptotic effects 22 of right ventricular cardiomyocytes that undergo apoptosis because of pressure overload 23 and of renal protective effects 24 against MCT toxicity, 2 should be informative.…”
Section: Circulation Journal Vol71 January 2007mentioning
confidence: 99%
“…23,24 A recent study also demonstrated that intramuscular injection of G-CSF induced angiogenesis through mechanisms independent of EPC mobilization. 25 These findings suggest that other possible mechanisms of G-CSF, such as direct angiogenesis and wound healing, may play a role.…”
Section: Mechanisms Of G-csf Effectmentioning
confidence: 93%